Halal Food as a Moral Forming Factor: A Review Comprehensive through Systematic Literature Review - Wathroh Mursyidi; Faznah Faznah (Bulletin of Pedagogical Research, 2025)
The phenomenon of globalization and the rise of modern lifestyles have significantly influenced consumption patterns, including food choices that often overlook the aspect of halal compliance. This study aims to systematically examine the relationship between halal food consumption and moral character development by integrating Imam Al-Ghazali’s perspective with contemporary scientific findings. The research employs a Systematic Literature Review (SLR) using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. The reviewed articles include both nationally accredited (Sinta) journals and internationally indexed (Scopus) publications. The findings indicate that consuming halal food holds not only religious value but also positive psychological and social implications. Hence, this study emphasizes the importance of halal consumption as a foundation for moral development and highlights the convergence between Islamic spiritual teachings and modern scientific evidence. This research contributes to the growing body of interdisciplinary studies connecting Islamic ethical thought with contemporary behavioral science. It offers a conceptual framework linking halal dietary practices to moral formation and provides theoretical insights for future empirical studies on the spiritual and psychological dimensions of halal consumption.